VIBRATION CONTROL OF A GANTRY CRANE SYSTEM USING DYNAMIC FEEDBACK SWING CONTROLLER - Md Yusop, Azdiana; Noor Asyikin, Sulaiman (2008)
The use of gantry crane system for transporting payload is very common in industrial application. However, moving the payload using the crane is not easy task especially when strict specifications on the swing angle and on the transfer time need to be satisfied. To overcome this problem a dynamic feedback swing controller is designed for the gantry position and speed, as well as the load angle and angular velocity using PID controller. Simulated responses of the position of the trolley and sway angle of the mass are presented using MATLAB. The performance of the Bangbang torque input function and the feedback swing controller are compared. From the simulation results, satisfactory vibration reduction of a crane system has been achieved using the proposed method.